Autonomic nervous system markers of music-elicited analgesia in people with fibromyalgia: A double-blind randomized pilot study - Lepping, Rebecca J.; McMillan, Miranda L.; Chadwick, Andrea L.; Mansour, Zaid M.; Martin, Laura E.; Gustafson, Kathleen M. (Frontiers in Pain Research, 2022)
Purpose: To investigate the feasibility of using music listening by adults with fibromyalgia (FM) as a potential tool for reducing pain sensitivity. Patients and methods: We report results from a double-blind two-arm parallel randomized pilot study (NCT04059042) in 9 participants with FM. Pain tolerance and threshold were measured objectively using quantitative sensory tests; autonomic nervous system (ANS) reactivity was measured with electrocardiogram. Participants were randomized to listen to instrumental Western Classical music or a nature sound control to test whether music listening elicits greater analgesic effects over simple auditory distraction. Participants also completed separate control testing with no sound that was counterbalanced between participants. Results: Participants were randomized 1:1 to music or nature sounds (4 Music, 5 Nature). Although the groups were not different on FM scores, the Music group had marginally worse temporal pain summation (p=.06), and the Nature group had higher Anxiety scores (p<.05). Outcome measures showed a significant difference between Groups in the magnitude of change in temporal summation between Sessions (p<.05) revealing that the Nature group had greater pain reduction during audio compared to silence, while the Music group had no difference between sessions. No significant effects were observed for either mechanical pain tolerance or ANS testing. Within the Music group, there was a trend of vagal response increase from baseline to music listening, but it did not reach statistical significance; this pattern was not observed in the Nature group. Conclusion: Auditory listening significantly altered pain responses. There may be greater vagal response to music versus nature sounds, however, results could be due to group differences in pain and anxiety. This line of study will help determine whether music could be prophylactic for people with FM when acute pain is expected.